A genomic catalog of cultivated bananas - Sardos, Julie; Cenci, Alberto; Rouard, Mathieu (2024)
Banana is an important food crop cultivated in many tropical and subtropical regions around the world. With the recent advances in genomics, a new powerful tool was developed enabling the fine-scale characterization of banana’s ancestry along chromosomes, i.e. chromosome painting.